KHALWAT DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Bukhari, Bukhari (State of Islamic Institute Langsa, 2018)
The existence of a man and woman who have no kinship so that it is lawful to marry her, in a lonely place without being ac companied by a mahram of the male or female side. This khalwat is a crime that is not subject to hudud punishment and kafarah punishment. This form of khalwat crime is included in the category of ta'zir finger whose number of punishment is not limited. In the Qur'an and Sunnah this khalwat act is highly reproached, but not clearly regulated in the Qur'an and Sunnah. So this act can be entered into the ta'zir group. All deeds that should (need) be forbidden to fulfill the common good (community). This prohibition must necessarily be made on the basis of community agreement / consensus in ways that are considered eligible. In North Aceh, the khalwat actors who are close to the power are hard to touch with the law, it is not surprising to all of us to remember that the law in this country is not yet the commander but the law is merely a bargaining position in everyday life.